2019
DOI: 10.1111/hsc.12822
|View full text |Cite
|
Sign up to set email alerts
|

On the path together: Experiences of partners of people with multiple sclerosis of the impact of lifestyle modification on their relationship

Abstract: Multiple sclerosis (MS) has a major impact on the relationship of couples living with the illness. Although some positives of dealing with MS as a couple have been identified, MS has been associated with higher rates of relationship breakdown and worse Quality of Life (QOL) for both people in the relationship, especially if the person with MS experiences a decline in mental or physical health or develops disability. Modification of lifestyle‐related risk factors has been associated with improved outcomes for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 43 publications
2
21
0
1
Order By: Relevance
“…We highly recommend inclusion of partners/significant others in educational sessions, as we have found this to be effective with respect to improving engagement and understanding the requirements of commitment to the study at home. In our studies, participants whose partners agreed to change their dietary habits to accommodate study recommendations reported greater ease of implementing the dietary intervention, as it increased the likelihood that a single meal could be prepared for the household rather than requiring separate meal preparation; these observations are largely consistent with findings from qualitative studies from other groups (Neate et al, 2019). Depending on the specifics of the intervention, the family dynamic, and prior dietary habits, it may or may not be feasible to extend the diet plan to include children or other household members.…”
Section: Self-directed Studysupporting
confidence: 80%
“…We highly recommend inclusion of partners/significant others in educational sessions, as we have found this to be effective with respect to improving engagement and understanding the requirements of commitment to the study at home. In our studies, participants whose partners agreed to change their dietary habits to accommodate study recommendations reported greater ease of implementing the dietary intervention, as it increased the likelihood that a single meal could be prepared for the household rather than requiring separate meal preparation; these observations are largely consistent with findings from qualitative studies from other groups (Neate et al, 2019). Depending on the specifics of the intervention, the family dynamic, and prior dietary habits, it may or may not be feasible to extend the diet plan to include children or other household members.…”
Section: Self-directed Studysupporting
confidence: 80%
“…Uncertainty about MS diagnosis, treatment, prognosis and management underpinned the experiences and concerns of people living with a person with MS. The unpredictable trajectory of MS was presented as a constant source of worry for partners, 43,44,46,47,51,58,68,70 carers, 25,[34][35][36]39,42,65 support persons, 23 Young carers felt unsupported and isolated.…”
Section: Living With Uncertaintymentioning
confidence: 99%
“…65 The most valued coping strategy was maintaining personal well-being and taking time out for themselves, 24,36,37,43,48,58,62,[65][66][67] and speaking to someone about their situation to relieve emotional tension. 23,26,28,47,51,58,65 Social support from friends and family members was a key enabler for children of a person with MS. 27,28,30,54,59,64 Some participants found that even though they might have been placed in situations outside their comfort zone, they learned to be adaptable, face challenges and develop new skills, 35,40,44,47,48,60,66,70,71 connect and communicate better with their partner 70 and reassess their lives to determine what they most valued. 66 Others learned to value and embrace their role as a carer, feeling a sense of pride and accomplishment.…”
Section: Adapting To Life With a Person With Msmentioning
confidence: 99%
“…Research to date has focused on the impact of MS on marriage or long-term relationships [4][5][6][7] However, there is currently a gap in the literature exploring the dating experiences of people with MS.…”
Section: Introductionmentioning
confidence: 99%